FAMILY INVOLVEMENT ON EFL STUDENTS’ INTERCULTURAL COMMUNICATIVE COMPETENCE DEVELOPMENT DURING LEARNING FROM HOME - Anugerah Febrian Syam; Andi Nurhikmah; Sumrah AP (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2021)
The purpose of the study is posed to diagnose the developmental stages of intercultural communicative competence during family interactions of Indonesian EFL higher education students at home context. An ethnographic approach with distant observation taken in this study due to the Covid-19 health protocol. A triangulation technique involving online interview and archival model was conducted to enhance the observation. The data collection was analyzed based on the Pyramid Model of Intercultural Competence (Deardroff, 2006) and the Developmental Model of Intercultural Sensitivity (Bennett, 2017). The result implies that the students’ intercultural communicative competence development viewing from the dimension of requisite attitudes covers valuing other cultures, openness to other people attitude, and tolerance in a different view. On another result, the dimension of knowledge and comprehension encompasses deep understanding and knowledge of contexts and worldviews, cultural self-awareness, and sociolinguistics awareness. In conclusion, EFL students' intercultural communicative competence development commonly promoted ethnorelative stages more than the ethnocentric stage.